BIBLIOGRAPHER KÂRLIS EGLE AND THE MAGAZINE “LATVJU GRÂMATA” (1922–1931) - JAUNMUKTANE, GUNTA (Knygotyra, 2015)
The magazine “Latvju Grāmata” is the first monthly magazine in the Latvian language covering literary criticism, book science and bibliography. During the ten years of the existence, it gave comprehensive overview of the Latvian and foreign book science of the respective time and also summarized and first published a lot of cultural and historical material on the Latvian cultural figures and the development of literature. The monthly published reviews, critiques of the recently published books, serious general articles on literature, literary history and theory; writers’ biographies, letters and notes; articles on bibliography and art of the book; research on languages; reviews of outstanding foreign fiction; wide chronicle of the Latvian literary activities; chronicle of theatre and art; extensive bibliography of recent books; information about Latvians in foreign literature; reviews of book publishing, conferences and other issues. Rūdolfs Egle (1889–1947), a man of letters and translator, was the editor-in-chief of the magazine. His brother Kārlis Egle (1887–1974), a bibliographer, literary historian and translator, was the main and sometimes the only doer and the actual editor of the magazine. Ansis Gulbis (1873–1936), a book publisher and writer, was the initiator and founder of the magazine. The Latvian Book Dealers and Publishers Society became the publisher of the magazine to make its activities comprehensive. The magazine was printed in different printing houses. The first number of the “Latvju Grāmata” was published in September 1922. The Society suffered material losses because of the little number of the readers, therefore it gave up the magazine. Ansis Gulbis urged Kārlis and Rūdolfs Egles to undertake the publication of the magazine in order to continue the monthly which the community needed. Rūdolfs Egle became the editor-in-chief and publisher of the magazine since its first number of 1927. Kārlis Egle worked hard and systematically for the “Latvju Grāmata”, and at the same time he compiled collected works of several writers, translated fiction from English and Russian, wrote reviews and essays on literary history, compiled bibliographies of writers, wrote the chapter of the Latvian literature for the Latvian encyclopaedia Latviešu konversācijas vārdnīca and worked as a director of the Misiņš Library since 1925. Kārlis Egle fell ill with tuberculosis due to the hard and stressful work, and the publication of the magazine had to be ceased. The last number of “Latvju Grāmata” was published in December 1931. “Latvju Grāmata” is still the only magazine on the Latvian bibliography and literary criticism that covered only these issues. The monthly published the valuable bibliography of the Latvian publications from 1922 to November 1931 (in the decimal classification system) compiled by the bibliographers Augusts Ģinters and Voldemārs Caune. “Latvju Grāmata”, as an important publication on the Latvian bibliography, literary history and criticism, has not lost its meaning up to nowadays. It gives very rich material and detailed reviews of literary activities of the respective period and is important to the contemporary literary critics and cultural historians. The magazine “Latvju Grāmata” can be considered as one of the magazines that started the Latvian bibliography and book science.